2018
DOI: 10.3390/rs10050805
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Vegetable Crop Parameter by Multi-temporal UAV-Borne Images

Abstract: 3D point cloud analysis of imagery collected by unmanned aerial vehicles (UAV) has been shown to be a valuable tool for estimation of crop phenotypic traits, such as plant height, in several species. Spatial information about these phenotypic traits can be used to derive information about other important crop characteristics, like fresh biomass yield, which could not be derived directly from the point clouds. Previous approaches have often only considered single date measurements using a single point cloud der… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
76
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 65 publications
(83 citation statements)
references
References 39 publications
2
76
1
Order By: Relevance
“…The total rainfall and mean temperature data of the monsoon cropping season varied from 2016 to 2018 (Table 1) [25]. [11]).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The total rainfall and mean temperature data of the monsoon cropping season varied from 2016 to 2018 (Table 1) [25]. [11]).…”
Section: Methodsmentioning
confidence: 99%
“…Timely fertiliser application with water supply is essential for a successful crop. Spectral data from Remote Sensing (RS) have been studied for many years for an adequate assessment of nutrient and water variability for yield optimisation [4][5][6] RS can be an effective tool in monitoring crop production [7-9] and estimating yield [10,11]. Early estimation of yield may allow better planning and forecasting the market prices and support food security based on the regional, national and global demand and supply.…”
mentioning
confidence: 99%
“…Forsmoo et al [14] calculated in a grassland sward, that for a plot of 8 m 2 a CH assessment with a ruler needed 550 single height measurements to receive the same accuracy as a SfM-based CH assessment based on UAV RGB imaging. Therefore, the high spatial resolution makes UAV RGB imagery in combination with an SfM approach an interesting tool for yield estimation in practical grassland farming.SfM derived height measurement based on UAV RGB imaging was successfully used in forestry [15], and, to a lower degree also in agricultural crops, such as wheat [6,16], barley [17], maize [18,19] and vegetable crops [20]. All these studies found strong relationships between biomass and RGB imaging in homogeneous crops.…”
mentioning
confidence: 99%
“…SfM derived height measurement based on UAV RGB imaging was successfully used in forestry [15], and, to a lower degree also in agricultural crops, such as wheat [6,16], barley [17], maize [18,19] and vegetable crops [20]. All these studies found strong relationships between biomass and RGB imaging in homogeneous crops.…”
mentioning
confidence: 99%
“…Bendig et al [60] estimated barley biomass using dynamic crop height data retrieved from a UAV, while Schirrman et al [61] evaluated the relationship among multiple biophysical parameters in wheat (i.e., multi-temporal crop height, LAI, nitrogen status and biomass). More recently, Moeckel et al [62] used the UAV-SfM approach to monitor vegetable crops (i.e., eggplants, tomatoes and cabbage). Despite the successful application of RGB imagery in UAV-based SfM approaches, all of the cited multi-temporal studies have used rotary UAVs, which have tended to limit the crop monitoring to relatively small field scales (i.e., they did not exceed 11 ha [61]).…”
Section: Introductionmentioning
confidence: 99%